SKRINING ANEMIA PADA LANSIA MELALUI PEMERIKSAAN HEMOGLOBIN DI WILAYAH KERJA PUSKESMAS DESA SUKASARI - Effendi Erfan; Yurman Yurman; Mardiyan Mardiyansyah (Asosiasi Institusi Pendidikan Tinggi Teknologi Laboratorium Medik Indonesia, 2022)
Hemoglobin is a protein in red blood cells that serves to transport oxygen from the lungs throughout the body. Hemoglobin may increase or decrease. Decreased hemoglobin levels in the blood called anemia. Decreased hemoglobin levels often occur in the elderly because of changes in the elderly body that cause damage to the bone marrow so that a decrease in the production of erythrocyte cells can result in a lack of hemoglobin in the body. Anemia is caused by many factors including bleeding, low nutrition, iron levels, folic acid, low vitamin B12 and problems in digestion and bone disorders. The purpose of this study is to know the picture of hemoglobin levels as screening anemia in elderly people aged 60-74 years in sukasari village in Seluma Regency. In this study using primary data with sampling techniques using purposive sampling. Examination directly using the Cyanmethemoglobin method. The results of the study obtained hemoglobin levels in seniors aged 60-74 years with a total of 30 samples obtained 17 samples with low hemoglobin levels with a percentage value of 56.7% , 12 samples have normal hemoglobin levels with a percentage of 40% and one sample high hemoglobin levels with a percentage of 3.3%.